Location-dependent role of phospholipase C signaling in the brain: Physiology and pathology. (January 2021) - Rusciano, Isabella; Marvi, Maria Vittoria; Owusu Obeng, Eric; Mongiorgi, Sara; Ramazzotti, Giulia; Follo, Matilde Y.; Zoli, Matteo; Morandi, Luca; Asioli, Sofia; Fabbri, Viscardo Paolo; McCubrey, James A.; Suh, Pann-Ghill; et al.
Abstract: Phosphoinositide-specific phospholipases C (PI-PLCs) are a class of enzymes involved in the phosphatidylinositol metabolism, which is implicated in the activation of several signaling pathways and which controls several cellular processes. The scientific community has long accepted the existence of a nuclear phosphoinositide (PI) metabolism, independent from the cytoplasmic one, critical in nuclear function control. Indeed, nuclear PIs are involved in many activities, such as cell cycle regulation, cell proliferation, cell differentiation, membrane transport, gene expression and cytoskeletal dynamics. There are several types of PIs and enzymes implicated in brain activities and among these enzymes, PI-PLCs contribute to a specific and complex network in the developing nervous system. Moreover, considering the abundant presence of PI-PLCβ1, PI-PLCγ1 and PI-PLCβ4 in the brain, a specific role for each PLC subtype has been suggested in the control of neuronal activity, which is important for synapse function, development and other mechanisms. The focus of this review is to describe the latest research about the involvement of PI-PLC signaling in the nervous system, both physiologically and in pathological conditions. Indeed, PI-PLC signaling imbalance seems to be also linked to several brain disorders including epilepsy, movement and behavior disorders, neurodegenerative diseases and, in addition, some PI-PLC subtypes could become potential novel signature genes for high-grade gliomas.